2017
DOI: 10.1002/elps.201700072
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic characterization and isolation of jellyfish stinging capsules

Abstract: Jellyfish stinging capsules known as nematocysts are explosive, natural-injection systems with high potential as a natural drug-delivery system. These organelles consist of a capsule containing a highly folded thin needle-like tubule and a matrix highly concentrated with charged constituents that enable the tubule to fire and penetrate a target. For the purpose of using these nematocysts as drug delivery system it is first required to purify subpopulations from heterogeneous population of capsules and to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…This approach was preferred over common biochemical methods such as centrifugation or Percol gradients because it yielded relatively large numbers of intact capsules, while offering high controllability and ease of operation. DEP-chip has been applied widely in biomedical research, bacteria detection and cell separation and its potential for jellyfish nematocyst characterization has recently been shown 46 49 ; but, it had not been used previously for cnidarian fractionations. We demonstrated that polar capsules had a distinct pDEP response in specific frequency ranges, which enabled their successful isolation and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was preferred over common biochemical methods such as centrifugation or Percol gradients because it yielded relatively large numbers of intact capsules, while offering high controllability and ease of operation. DEP-chip has been applied widely in biomedical research, bacteria detection and cell separation and its potential for jellyfish nematocyst characterization has recently been shown 46 49 ; but, it had not been used previously for cnidarian fractionations. We demonstrated that polar capsules had a distinct pDEP response in specific frequency ranges, which enabled their successful isolation and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…6A). Having potential in drug delivery methods, this study aimed at characterizing these capsules for DEP separation [100]. In this study, they characterized larges capsules with both single‐ and two‐shell models (Fig.…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 99%
“…The symbols are experimental measurements while the solid lines are the fitted two‐shell model. Reprinted with permission from [100], copyright 2017, John Wiley and Sons.…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 99%
“…The DEP manipulation is dependent on the polarization factor or the Clausius-Mossotti factor (CMF) of particle and on the medium interaction. Recently, the DEP method has been applied in microbiological research to isolation (Park et al, 2017;Cheng et al, 2015), concentration (Koklu et al, 2017;Hsiung et al, 2008) and localization (Kim et al, 2017;Kinio et al, 2017) of particles by implementing focusing (Nakano et al, 2011) and trapping (Chen et al, 2018) manipulation mechanism. Meanwhile, it is able to use for developing biosensor and biosensing on artificial microbeads (Han et al, 2017), biological cells (Iswardy et al, 2017;Kim et al, 2015) and pharmaceutical delivery (Li et al, 2017) applications.…”
Section: Introductionmentioning
confidence: 99%